Antimicrobial and teat sealant use and selection criteria at dry-off on Canadian dairy farms - Kayley D. McCubbin; Ellen de Jong; Carmen M. Brummelhuis; Julia Bodaneze; Marit Biesheuvel; David F. Kelton; Tamaki Uyama; Simon Dufour; Javier Sanchez; Daniella Rizzo; David Léger; Herman W. Barkema (Journal of Dairy Science, 2023)
ABSTRACT: Infections with antimicrobial resistant pathogens are a major threat to human and animal health worldwide. Further, reduction of livestock-associated antimicrobial use (AMU) is often identified as an area of focus. Selective dry cow therapy (DCT) warrants consideration as an important way to decrease AMU on Canadian dairy farms. In addition, teat sealants (TS) are a nonantimicrobial alternative for prevention of intramammary infection during the dry period. Therefore, objectives of this study were to determine how antimicrobials and TS are used at dry-off on Canadian dairy farms to determine selective DCT uptake and enacted selection protocols. It was expected that these data will provide a baseline understanding of DCT practices and highlight areas for future intervention to further reduce AMU. An observational study was conducted utilizing 2 in-person questionnaires conducted between July 2019 and September 2021 on 144 participating dairy farms in 5 Canadian provinces (British Columbia = 30, Alberta = 30, Ontario = 31, Québec = 29, and Nova Scotia = 24). Overall, 45 farms (31%) reported adopting selective DCT, 95 (66%) enacted blanket DCT, and 4 (3%) did not provide antimicrobial DCT. Farms enacting selective DCT had approximately 50% less intramammary antimicrobials used at dry-off compared with blanket DCT farms. Cow somatic cell count history was the most common criterion for selective DCT decision-making, followed by previous clinical mastitis history, bacteriological culture, and milk production. A slight majority of farms (56%) applied TS to all cows at dry-off, whereas 17 farms (12%) used TS selectively, and 46 farms (32%) did not use TS. Larger herds more often used TS, and farms with an automatic milking system more often used TS selectively than applied to all cows. Results highlighted the variability in antimicrobial treatment and TS use protocols at dry-off on Canadian dairy farms, and the potential for further antimicrobial reduction with increased adoption of selective DCT.